Interactions among patch area, forest structure and water fluxes in a fog-inundated forest ecosystem in semi-arid Chile - Barbosa, Olga; Marquet, Pablo A; Bacigalupe, Leonardo D; Christie, Duncan A; del-Val, Ek; Gutierrez, Alvaro G; Jones, Clive G; Weathers, Kathleen C; Armesto, Juan J (Functional ecology, 2010)
1. The area or size of an ecosystem affects the acquisition, storage and redistribution of energy and matter. Patch size reduction due to natural or anthropogenic habitat loss will not only modify species distribution and patch structure but also affect the ecosystem processes that are, in part, responsible for patch persistence. 2. In a fog-dependent forest ecosystem, trees and their architectures play essential roles in capturing and redistributing water from collection surfaces. In this paper, we address the question of how forest patch size and structure interact to determine fog water inputs and storage in a fog-inundated, coastal ecosystem in semi-arid Chile (30°S). 3. Six forest patches ranging in area from 0·2 to 36 ha on a coastal mountaintop of Fray Jorge National Park were characterized using 0·1 ha plots laid down at the centre of each forest patch. In each patch, we assessed tree basal area as a measure of forest structure, recorded daily air temperature and humidity, measured water influx from stemflow and throughfall (water that has passed through the forest canopy). Soil and litter gravimetric water contents were used as a measure of storage. 4. Total tree basal area per hectare was positively related to patch area, despite some variation at the species level. Mean and maximum air temperatures inside the patches were inversely related to patch size, with maximum temperatures differing by 2 °C on average. Annual fog water capture by trees within forest patches (net throughfall) was estimated in 296·1 mm after rain flux (about 122 mm) was subtracted. Throughfall volume and patch area were uncorrelated, but stemflow volume, soil and litter water contents scaled positively with patch area, showing a functional link between water interception and ecosystem retention. 5. Our study shows that ecosystem area in this mosaic of fog-dependent temperate forest patches can modify water fluxes and storage capacity of the ecosystem. This finding has important consequences for fragmented landscapes, where large continuous forests are fragmented into smaller patches, affecting not only the persistence of species but also the continuity of critical ecosystem processes.